The Influence of Workload, Job Stress and Job Insecurity upon Turnover Intention (Study on Sewer Employees of PT X Semarang) - Mulyani, Dwi -; Karnowahadi, Karnowahadi -; TriJoga, Josef Bambang (Admisi dan Bisnis, 2021)
Based on the research background, the problem of this research is employees working in the general section of sewer who experience changes every month and exceed the maximum limit of the turnover rate in the company, playing more that 3% in 2019. The purpose of this study is to see the effect of workload, job stress and job insecurity both partially and simultaneously on employees’ turnover intention at PT X Semarang. Data collecting methods in this research using questionnaires and literature study. The sample in this study were 93 employees of the general sewer section of PT X Semarang. The data analysis technique used was multiple regression. From the multiple regression analysis in this study, it can be found that workload, job stress and job insecurity affect the employees’ turnover intention. the most dominant variable affecting turnover intention is job insecurity. The magnitude of the coefficient of determination on the variable workload, job stress and job insecurity have an effect on turnover intention with adjusted R Square 0f 0,468. It could show that the influence of workload variable, job stress and job insecurity were 46,8% while the remaining 53,2 % is by other models not examined in this regression model.